Development of a quality-based irrigation water security index - Dina El Demerdash; Mohie El Din Omar; Mohamed Nour El-Din; Hesham El-Badry; Essam Aly; Doaa A. El-Molla (Ain Shams Engineering Journal, 2022)
This paper introduces a new concept for water security, the Irrigation Water Security Quality-based Index. Through this concept, the irrigation water security is presented based on quantity and quality. The effect of water quality parameters on agriculture productivity, soil deterioration, and public health was evaluated. The probability of harm was used in the risk analysis and assessment. The developed index was applied to evaluate the Egyptian irrigation system, 10% reduction in the Nile’s supply, and four adaptation scenarios as an illustrative example. Drainage water reuse is adopted in Egypt to provide a sufficient supply and improve the water security. However, this improved water security doesn’t consider the water’s quality. The current Egyptian condition and 10% Nile reduction showed water insecurity. Expanding drainage and sewage water treatment improved the developed index to high security levels. This highlights the importance of drainage water treatment in attaining a sustainable high water security level.